Revision of the subgenus Tinotus Sharp, stat. n., of the parasitoid rove-beetle genus Aleochara Gravenhorst (Coleoptera, Staphylinidae, Aleocharinae) from Japan, Taiwan, and the Russian Far East - Yamamoto, Shûhei (Zookeys, 2016)
Abstract. The subgenus Tinotus Sharp, 1833, stat. n., of the genus Aleochara Gravenhorst, 1802 (Aleocharini: Aleocharina) from Japan, Taiwan, and the Russian Far East is revised. Tinotus is a new record from the latter two regions. Three species are recognized: Aleochara (Tinotus) morion Gravenhorst, 1802, comb. n. [Japan (new record), the Russian Far East (new record)], Aleochara (Tinotus) eoa nom. n. [replacement name for Tinotus japonicus Cameron, 1933; Japan, Taiwan (new record)], and Aleochara (Tinotus) takashii sp. n. (central Honshû, Japan). The systematic position of Tinotus is discussed. All species are (re-)described, keyed, and figured. A world checklist of Tinotus species, comprising 40 valid species, is provided in an appendix. Additional taxonomic changes are proposed, including a new synonymy, a revalidation, 13 new replacement names, and 27 new combinations.